Parenting Strategies to Overcome Gadget Addiction in Children: A Case Study at TK Negeri Pembina Bantarbolang, Peguyangan Village - Novilia, Shindy Arizka; Widyarti, Alifa Khayrani; Arrohman, Aden Yunar; Isbah, Faliqul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study investigates the effectiveness of parenting strategies in mitigating early childhood gadget addiction at TK N Pembina Bantarbolang, Peguyangan Village. Conducted as part of a Real Work Lecture (KKN) initiative, the program featured an educational session led by Mrs. Lisa Devi Dian Arifia, S. Psi, M. Psi, a lecturer from UIN Abdurrahman Wahid Pekalongan. The session aimed at equipping parents with an understanding of the adverse effects of excessive gadget use on young children and practical techniques to manage their children’s screen time. Mrs. Arifia highlighted the widespread nature of gadget addiction and its potential to hinder children’s social skills, cognitive development, and overall well-being. Through empirical data and real-life examples, she emphasized the urgency of addressing this issue. Key strategies discussed included fostering open communication between parents and children, setting clear guidelines for gadget usage, and promoting alternative activities that encourage creativity and physical engagement. The study’s findings demonstrated the efficacy of these strategies in reducing children’s reliance on electronic devices when implemented consistently. Parents who practiced open communication and set structured limits on screen time observed significant improvements, such as increased participation in outdoor activities and creative play. This research underscores the vital role of informed and proactive parenting in addressing early childhood gadget addiction. By adopting these strategies, parents can foster a supportive and engaging environment that mitigates the risks of excessive screen time and promotes healthier developmental outcomes for their children.